WRKY76 is a rice transcriptional repressor playing opposite roles in blast disease resistance and cold stress tolerance - Yokotani, Naoki (Oxford University Press, 2013)
OsWRKY76 encodes a group IIa WRKY transcription factor of rice. The expression of OsWRKY76 was induced within 48h after inoculation with rice blast fungus (Magnaporthe oryzae), and by wounding, low temperature, benzothiadiazole, and abscisic acid. Green fluorescent protein-fused OsWRKY76 localized to the nuclei in rice epidermal cells. OsWRKY76 showed sequence-specific DNA binding to the W-box element in vitro and exhibited W-box-mediated transcriptional repressor activity in cultured rice cells. Overexpression of OsWRKY76 in rice plants resulted in drastically increased susceptibility to M. oryzae, but improved tolerance to cold stress. Microarray analysis revealed that overexpression of OsWRKY76 suppresses the induction of a specific set of PR genes and of genes involved in phytoalexin synthesis after inoculation with blast fungus, consistent with the observation that the levels of phytoalexins in the transgenic rice plants remained significantly lower than those in non-transformed control plants. Furthermore, overexpression of OsWRKY76 led to the increased expression of abiotic stress-associated genes such as peroxidase and lipid metabolism genes. These results strongly suggest that OsWRKY76 plays dual and opposing roles in blast disease resistance and cold tolerance.